Применение метода интраоперационной микроскопии в хирургическом лечении периапикальных корневых кист (Эндодонтия Today, 2020)
Clinical examination of 30 patients after surgical treatment of periapical cysts was carried out at the Department of the Departmental Surgical Dentistry and Implantology in Clinical Diagnostic Center of Moscow University of Medicine and Dentistry. Patients were divided into 3 groups, 10 persons in each group. Patients in group №1 were treated using traditional surgical approach. Retrograde filling technique was used in group №2. The use of dental operating microscope and microsurgical techniques were applied in group №3. Patients were monitored throughout a 1,5 year recall period. The criteria of treatment effectiveness, was based on asymptomatic clinical appearence and evidence of radiograph bone healing. The outcome of the study showed high effectiveness of surgical periapical cysts treatment using dental operating microscope.